Waste plastic to pyrolytic oil and its utilization in CI engine: Performance analysis and combustion characteristics. (15th February 2020) - Singh, R.K.; Ruj, Biswajit; Sadhukhan, A.K.; Gupta, P.; Tigga, V.P.
Highlights: Utilization of crude PPO in different blend ratio with diesel. A blend of 50% PPO with diesel gives an increased BTE and lower SFC. Addition of PPO with diesel increases heat release rate and cylinder pressure. Reduction in emission of NOX and UHC is observed at high loads. High load results in increased CO and reduced CO2 . Abstract: For application of pure plastic pyrolytic oil (PPO) several modifications in the engine is required which rejects the utilization of the existing engines while a blend of conventional fuel and PPO can be used with a slight change in engine without having a high impact on engine performance and hence the blends are preferred over the utilization of PPO as crude oil for diesel engines. In this study, the non-catalytic pyrolysis of mixed plastic waste at a temperature of 450 °C is done to obtain high-grade pyrolytic oil having a composition similar to petroleum fuels such as gasoline and diesel. Physical properties of the PPO were analysed, and the compound analysis was done with GC–MS. Further FTIR of PPO and diesel were analysed and compared. Five different ratios of 10, 20, 30, 40 and 50% PPO with diesel in blends were utilized as a fuel in a diesel engine to determine the engine performance and characteristics. The higher presence of PPO in blend increases the brake thermal efficiency (BTE) and reduces specific fuel consumption (SFC) with an increase in load as reported. The presence of PPO results in high heat release and delayed ignition resulting in high in-cylinder pressure. Further high amount of oxygenated compounds in PPO helps in reducing the emission from the combustion. The utilization of PPO with diesel upto 50% in the blend can be used in diesel engines with a slight increase in emission of CO at higher loads.